Quelques notes sur Pierre Bec éditeur critique du texte occitan médiéval - Gilda Caiti-Russo (Lengas)
To focus on the way people edit medieval occitan texts is like making a scientific portrait of critical editors. Pierre Bec‘s secondary PHD thesis was on the Saluts d’amour du troubadour périgourdin Arnaut de Maruelh. This philological edition reveals that philological work on old occitan can get information from study on contemporary occitan diatopic variation, which was the subjet of Bec’s first PHD theses : Les Interférences linguistiques entre gascon et languedocien dans les parlers du Comminges et du Causerans. The other way round, medieval occitan lets Bec anticipate, by its proto-system notion, diasystemic functions in grafic models applied to contemporary occitan.